Cardiometabolic Changes in Response to a Calorie-Restricted DASH Diet in Obese Older Adults - Perry, Cydne A.; Van Guilder, Gary P.; Hossain, Mosharraf; Kauffman, Alyssa (Frontiers in Nutrition, 2021)
Objective: To examine the response of a calorie-restricted Dietary Approaches to Stop Hypertension diet on indicators of cardiometabolic health in a cohort of sedentary obese older adults. Design: This was a controlled-feeding trial with a parallel design. Each participant consumed either 3 oz (85 g; n = 15) or 6 oz (170.1 g; n = 13) of lean fresh beef within a standardized calorie-restricted DASH-like diet for 12-weeks. Fasted blood samples were collected and used to measure conventional biomarkers of cardiovascular, metabolic and inflammatory health. Participants: Caucasian older (70.8 years), obese (BMI: 32 ± 6.9 kg/m2; WC: 101 ± 16.4 cm) females (n = 17) and males (n = 11) from the rural community of Brookings, South Dakota. Results: 28 participants completed the 12-week feeding trial, with no differences (p > 0.05) among the biomarkers of cardiometabolic health between the 3 and 6 oz beef intake groups. However, when the beef intake groups were combined, all biomarkers changed concentration in response to the intervention diet. Total cholesterol (p < 0.001), LDL-C (p = 0.004), HDL-C (p < 0.0001), insulin (p = 0.014), glucose (p = 0.008), HOMA-IR (p < 0.05), IL-12 (p < 0.001), and CRP (p = 0.006) all decreased in response to the study diet. IGF-1 (p < 0.001) and IL-8 (p = 0.005) increased in response to the intervention. Correlations among cardiometabolic biomarkers and body composition measures were observed. By study end, the decrease in insulin (R2 = 0.22; P = 0.012) and HOMA-IR (R2 = 0.22; P = 0.01) was positively correlated with the decrease in waist circumference. The increase in IGF-1 was significantly correlated with the decrease in waist circumference (R2 = 0.21; p = 0.014). The increase in IGF-1 was significantly correlated with the increase in sit-to-stand (R2 = 0.21; p = 0.016). The increase in IL-8 was significantly correlated with decreases in total cholesterol (R2 = 0.24; P = 0.008), LDL-C (R2 = 0.17; P = 0.031) and glucose (R2 = 0.44; P = 0.0001). Conclusions: These findings suggest that a DASH-like diet with restricted calories may potentially improve biomarkers of cardiometabolic health in sedentary obese older adults. These results also point to interrelationships between body composition changes and changes in cardiometabolic biomarkers. Lastly, regardless of meat intake amount, positive impacts on cardiometabolic biomarkers were observed in this cohort of older adults with an obese phenotype.